Intraguild predation enhances biodiversity and functioning in complex food webs - Wang S, Brose U, Gravel D (Ecology, 2019)
Intraguild predation (IGP), i.e. feeding interaction between two consumers that share the same resource species, is commonly observed in natural food webs. IGP expands vertical niche space and slows down energy flows from lower to higher trophic levels, which potentially affects the diversity and dynamics of food webs. Here, we use food web models to investigate the effects of IGP on species diversity and ecosystem functioning. We first simulate a five‐species food web module with different strengths of IGP at the herbivore and/or carnivore level. Results show that as the strength of IGP within a trophic level increases, the biomass of its resource level increases because of predation release; this increased biomass in turn alters the energy fluxes and biomass of other trophic levels. These results are then extended by subsequent simulations of more diverse food webs. As the strength of IGP increases, simulated food webs maintain (1) higher species diversity at different trophic levels, (2) higher total biomasses at different trophic levels, and (3) larger energy fluxes across trophic levels. Our results challenge the intuitive hypothesis that food web structure should maximize the efficiency of energy transfer across trophic levels; instead, they suggest that the assembly of food webs should be governed by a balance between efficiency (of energy transfer) and persistence (i.e. the maintenance of species and biomasses). Our simulations also show that the relationship between biodiversity and ecosystem functioning (e.g. total biomass or primary production) is much stronger in the presence of IGP, reconciling the contrast from recent studies based on food‐chain and food‐web models. Our findings shed new light on the functional role of IGP and contribute to resolving the debate on structure, diversity and functioning in complex food webs. This article is protected by copyright. All rights reserved.